OPTIMALIZATION OF WINDOW WIDTH AND WINDOW LEVEL ON LUNG WINDOW FOR ANATOMIC INFORMATION CT SCAN THORAX OF LUNG TUMORS CASE IN RSUD TUGUREJO PROVINCE OF CENTRAL JAVA - Anggraini Dwi S; Rasyid Rasyid; Darmini Darmini (Jurnal Imejing Diagnostik (JImeD), 2018)
Background: Settings for Window Width and Window Levels used in CT Scan Thorax tumor cases vary. On Seimens 128 Slice plane there are standard settings for lung window thorax is with Window Width 2200 HU and Window Level -200 HU while according to window width theory is 1000- 2000 HU value range and window level -200--800 HU. The purpose of this research is to know the difference of variation setting Window Width and Window Level on Lung Window and Window Width and Window Level optimum in producing anatomical information CT scan thoraks in case of lung tumor.Method: The type of research conducted in the writing of this final task is quantitative research using experimental approach. Data were collected on 5 patients suspected of lung tumor, then variation of setting window width and window level. The result of variation of window width and window level setting was then evaluated by 2 observers to obtain anatomical information of CT Scan Thorax in lung tumor case then analyzed by using Friedman Test different from spss version 16.0.Result: The result of the research resulted the difference of Window Width and Window Level was assessed from p value α (0.05). the value of significance p value 0.001 which means there is a difference. Highest mean mean value with value 8.25 in window width 1800 HU and window level -200 HU. The use of the most optimal setting variation is the Window Width 1800 HU and Window Level -200 HU because it can provide anatomical image information of CT Scan Thoraks optimal lung tumor cases where the anatomy of the pulmonary, broncus, trachea, aortic mass, pulmonary and chest lung par clearly visible and bordered on axial pieces.